Public awareness, attitudes, beliefs, and behaviors regarding the role of pharmacists as immunizers - A. M. Di Castri; D. M. Halperin; L. Ye; D. MacKinnon-Cameron; M. Kervin; J. E. Isenor; S. A. Halperin (Human Vaccines & Immunotherapeutics, 2021)
Vaccine coverage is below desired levels in Canada, despite National Advisory Committee on Immunization recommendations. One solution to improve coverage is to offer vaccines in pharmacies. We explore the awareness, attitudes, beliefs, and behaviors of the general public in four communities in Nova Scotia (NS) and New Brunswick (NB) about the changing role of pharmacists as immunizers. Adult members of the public were invited to complete an online survey through advertisements in print and online, and through e-mail lists at local universities. Immunization status among participants (n = 985) varied across vaccines with slightly more than one-half of the participants (51.8%) reporting receipt of a seasonal influenza vaccine last year, 38.0% reporting receipt of the meningococcal C or ACWY vaccine, and 77.7% reporting receipt of the pertussis vaccine. Despite variable self-reported receipt of vaccines, the pervasive belief that participants were not at risk of getting vaccine-preventable diseases, and a lack of awareness about which vaccines are recommended for adults, participants in this study held vaccine-positive beliefs. Participants, especially those who had previously been vaccinated in a pharmacy (39.0%), were supportive of the inclusion of pharmacists as immunizers although nearly one-half of the participants would feel more comfortable getting vaccinated by a pharmacist if another practitioner recommended it to them. While cost threatens to be a barrier to pharmacists as immunizers, this study suggests that they are well-positioned to improve vaccine coverage and to communicate recommendations and other vaccine-related information to the public.